Relationship between coping and university adjustment and academic achivement amongst First Year Undergraduates in Malaysian Public University. - Abdullah, Maria Chong; Elias, Habibah; Uli, Jegak; Mahyuddin, Rahil (InternationalJournal, 2010)
This study aimed to investigate the relationship between coping efforts amongst first year undergraduates and their university adjustment and academic achievement. 250 first year students attending various undergraduate programs at a Malaysian public university participated in this study. The study employed a correlation design and data was analyzed using descriptive and inferential statistics to address the research objectives. Findings from this study showed that there is a significant and positive relationship between students’ coping and their overall university adjustment, academic adjustment, social adjustment, personal-emotional adjustment, students’ attachment to the university, and academic achievement. Results also indicated that throughout a period of one semester, students’ overall adjustment and academic achievement was found to be significantly predicted by their coping strategies.